Reelle Subsumtion und Insubordination im Zeitalter der digitalen Maschinerie: Mit-Untersuchung der Streikenden bei Amazon in Leipzig - Barthel, Georg; Rottenbach, Jan (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2017)
The article presents the results of ongoing co-research at the fulfilment centre of Amazon in Leipzig. It demonstrates exemplarily that despotic forms of labour are a central feature also of digital capitalism. Amazon is implementing various strategies of real subsumption to get the workers functioning as a senso-motoric part of the digital machinery in order to exploit their labour power. It is monopolizing the knowledge about the production process, setting up the FC as a panoptic factory and producing an internal public. This however encounters moments of insubordination resulting in daily micro-conflicts over working conditions and capitalist commands. Workers try to withdraw themselves from the despotism of the factory, use primitive forms of sabotage and develop a counter-public.